Does participation in art classes influence performance on two different cognitive tasks? - Schindler, Manuel; Maihöfner, Christian; Bolwerk, Anne; Lang, Frieder (Aging & Mental Health, 2016)
Objectives: Effects of two mentally stimulating art interventions on processing speed and visuo-spatial cognition were compared in three samples. Method: In a randomized 10-week art intervention study with a pre-post follow-up-design, 113 adults (27 healthy older adults with subjective memory complaints, 50 healthy older adults and 36 healthy younger adults) were randomly assigned to one of two groups: visual art production or cognitive art evaluation, where the participants either produced or evaluated art. ANOVAs with repeated measures were computed to observe effects on the Symbol-Digit-Test, and the Stick Test. Results: Significant Time effects were found with regard to processing speed and visuo-spatial cognition. Additionally, there was found a significant Time x Sample interaction for processing speed. The effects proved robust after testing for education and adding sex as additional factor. Conclusion: Mental stimulation by participation in art classes lead to an improvement of processing speed and visuo-spatial cognition. Further investigation is required to improve understanding of the potential impact of art intervention on psychological functioning across adulthood.
Keywords: subjective memory complaints; visual arts; mental stimulation; processing speed; visuo-spatial cognition

Does participation in art classes influence performance on two different cognitive tasks? - Schindler, Manuel; Maihöfner, Christian; Bolwerk, Anne; Lang, Frieder (Aging & Mental Health, 2017)
OBJECTIVES: Effects of two mentally stimulating art interventions on processing speed and visuo-spatial cognition were compared in three samples. METHOD: In a randomized 10-week art intervention study with a pre-post follow-up design, 113 adults (27 healthy older adults with subjective memory complaints, 50 healthy older adults and 36 healthy younger adults) were randomly assigned to one of two groups: visual art production or cognitive art evaluation, where the participants either produced or evaluated art. ANOVAs with repeated measures were computed to observe effects on the Symbol-Digit Test, and the Stick Test. RESULTS: Significant Time effects were found with regard to processing speed and visuo-spatial cognition. Additionally, there was found a significant Time × Sample interaction for processing speed. The effects proved robust after testing for education and adding sex as additional factor. CONCLUSION: Mental stimulation by participation in art classes leads to an improvement of processing speed and visuo-spatial cognition. Further investigation is required to improve understanding of the potential impact of art intervention on cognitive abilities across adulthood.
EVALuna2:36362

How art changes your brain: differential effects of visual art production and cognitive art evaluation on functional brain connectivity - Bolwerk, Anne; Mack-Andrick, Jessica; Lang, Frieder; Maihöfner, Christian; Dörfler, Arnd (PLoS ONE, 2014)
Visual art represents a powerful resource for mental and physical well-being. However, little is known about the underlying effects at a neural level. A critical question is whether visual art production and cognitive art evaluation may have different effects on the functional interplay of the brain's default mode network (DMN). We used fMRI to investigate the DMN of a non-clinical sample of 28 post-retirement adults (63.71 years ±3.52 SD) before (T0) and after (T1) weekly participation in two different 10-week-long art interventions. Participants were randomly assigned to groups stratified by gender and age. In the visual art production group 14 participants actively produced art in an art class. In the cognitive art evaluation group 14 participants cognitively evaluated artwork at a museum. The DMN of both groups was identified by using a seed voxel correlation analysis (SCA) in the posterior cingulated cortex (PCC/preCUN). An analysis of covariance (ANCOVA) was employed to relate fMRI data to psychological resilience which was measured with the brief German counterpart of the Resilience Scale (RS-11). We observed that the visual art production group showed greater spatial improvement in functional connectivity of PCC/preCUN to the frontal and parietal cortices from T0 to T1 than the cognitive art evaluation group. Moreover, the functional connectivity in the visual art production group was related to psychological resilience (i.e., stress resistance) at T1. Our findings are the first to demonstrate the neural effects of visual art production on psychological resilience in adulthood.